Blockholder Scarcity, Takeovers, and Ownership Structures - Gorton, Gary; Kahl, Matthias (Journal of Financial and Quantitative Analysis, 2008)
Abstract Agency problems in firms are prevalent because of a scarcity of wealthy principals with corporate governance ability, whom we call “restructuring specialists.” We investigate how this scarce resource, “agency cost-free capital,” is allocated. We show that the restructuring specialists may acquire blocks only in those states of the worls in which they can increase firm value the most, which corresponds to a takeover. Firms with dispersed ownership and firms with a financial intermediary as a blockholder can coexist, although they are otherwise identical. The moderl can explain differences in corporate ownership structures and restructuring mechanisms across economies.